2009
DOI: 10.1246/cl.2009.1188
|View full text |Cite
|
Sign up to set email alerts
|

Stable Sulfenyl Iodide Bearing a Primary Alkyl Steric Protection Group with a Cavity-shaped Framework

Abstract: A primary alkyl steric protection group bearing a cavity-shaped framework, a BpqCH2 group, was developed. A sulfenyl iodide with the BpqCH2 group was successfully synthesized and unambiguously characterized by X-ray crystallographic analysis. The sulfenyl iodide showed remarkable stability both in the solid state and in solution, demonstrating that the BpqCH2 group is promising for kinetic stabilization of primary alkyl substituted reactive species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…[11] We found that the BpqCH 2 group is effective for kinetic stabilization of reactive species which otherwise undergo facile bimolecular decomposition such as a sulfenyl iodide (X = SI). In this context, we set out to prepare a primary-alkyl-substituted selenenic acid by utilizing this substituent.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[11] We found that the BpqCH 2 group is effective for kinetic stabilization of reactive species which otherwise undergo facile bimolecular decomposition such as a sulfenyl iodide (X = SI). In this context, we set out to prepare a primary-alkyl-substituted selenenic acid by utilizing this substituent.…”
mentioning
confidence: 95%
“…The synthesis of a primary-alkyl-substituted selenenic acid was achieved by thermal b elimination from a selenoxide. [12] The selenoxide precursor 4 was prepared from the bromide 1 [11] as outlined in Scheme 3. After scrutiny of the reaction conditions for thermolysis of 4, we found that heating 4 in the solid state at 80 8C in vacuo cleanly produced the desired selenenic acid 5 (Scheme 4).…”
mentioning
confidence: 99%
“…It is a common idea, however, that the steric demands of primary-alkyl groups are too small to protect such reactive species, and there has been no example of the synthesis of a primary-alkyl-substituted selenenyl iodide. In the course of our studies on biologically relevant, highly reactive species derived from thiols and selenols, we recently developed a primary-alkyl steric protection group, a BpqCH 2 group (Figure 1), with a cavity-shaped framework [11]. Despite being a primary-alkyl group, this substituent was found to be effective for the stabilization of reactive species such as a sulfenic acid (X = SOH) [12], a sulfenyl iodide (X = SI) [11], and a selenenic acid (X = SeOH) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our studies on biologically relevant, highly reactive species derived from thiols and selenols, we recently developed a primary-alkyl steric protection group, a BpqCH 2 group (Figure 1), with a cavity-shaped framework [11]. Despite being a primary-alkyl group, this substituent was found to be effective for the stabilization of reactive species such as a sulfenic acid (X = SOH) [12], a sulfenyl iodide (X = SI) [11], and a selenenic acid (X = SeOH) [13]. Here we report the synthesis of a stable primary-alkyl-substituted selenenyl iodide by utilizing this molecular cavity and its hydrolytic conversion to the corresponding selenenic acid; hydrolysis of a selenenyl iodide to a selenenic acid has been proposed to be potentially involved in the second half-reaction of ID-3 [14], but no chemical evidence has been available for this reaction process.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, compounds that contain chromanone moiety constitute an important class of naturally occurring substances 6 and draw the attention of many researches due to their wellknown properties as having antiviral activities [7][8][9][10][11][12] The present work is also prompted by the previously well-established results describing the regioselective behavior of various 1,3-dipole systems with thione-containing compounds. 4 is in accordance with previous reported results where α-oxo thioketone compounds in dimeric form were prepared by a similar procedure.…”
Section: Introductionmentioning
confidence: 99%